LAYANAN BIMBINGAN BELAJAR SEBAGAI UPAYA PENINGKATAN KUALITAS PROSES BELAJAR-MENGAJAR - Zaenal Abidin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
According to the real result of the various studying difficulties, which being felt by the client (student), whatever their reasons or motives are very much demand to the guider to take part in looking for the various alternatives in order to help the student resolving those cases through the learning guidance services actively. This activity is in order to create the student’s mental stability and their readiness to promote their aptitude and full participation, especially in learning process (in the class). If this condition can be realized be expected to obtain the quality of learning-teaching process in the class. Kata kunci: learning guidance, learning process, enhancing learning quality effort.